Effect of supplemental carbohydrate source on the utilization of low-quality tallgrass-prairie hay by beef steers - Heldt, J.S.; Cochran, R.C.; Farmer, C.G.; Mathis, C.P.; Titgemeyer, Evan C.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twenty ruminally fistulated steers were used in different two experiments to evaluate the effects of supplemental carbohydrate source (starch, glucose, fructose, or sucrose) fed at .3% BW/day on the utilization of low-quality tallgrass-prairie hay. In Experiment 1, all supplemental carbohydrates were fed with a low level of supplemental degradable intake protein. In Experiment 2, the level of supplemental degradable intake protein was high. Intake of the tallgrass-prairie hay was not affected significantly by supplementation in either experiment, but as a result of the added carbohydrate, total intake was increased. When supplemental protein intake was inadequate, supplemental carbohydrates depressed digestion, but when supplemental protein was higher, fiber digestion was not depressed. Because of increased total intake (forage plus supplement) and increased digestion in Experiment 2, total digestible organic matter intake was greater in the supplemented animals, with little difference among carbohydrate sources.
Keywords: Beef; Steers; Forage; Starch; Sugar